Research on the biological mechanism and potential application of CEMIP - Liu, Yang; Hu, Gang; Li, Yuetong; Kong, Xinyi; Yang, Kaming; Li, Zhenlin; Lao, Wanwen; Li, Jiaxin; Zhong, Jianhua; Zhang, Shitong; Leng, Yuxin; Bi, Changlong; et al. (Frontiers in Immunology, 2023)
Cell migration-inducing protein (CEMIP), also known as KIAA1199 and hyaluronan-binding protein involved in hyaluronan depolymerization (HYBID), is a new member of the hyaluronidase family that degrades hyaluronic acid (HA) and remodels the extracellular matrix (ECM). In recent years, some studies have reported that CEMIP can promote the proliferation, invasion and adhesion of various tumor cells, and play an important role in bacterial infection and arthritis. This review focuses on the pathological mechanism of CEMIP in a variety of diseases and expounds the function of CEMIP from the aspects of inhibiting cell apoptosis, promoting HA degradation, inducing inflammatory responses, related phosphorylation, adjusting cellular microenvironment and regulating tissue fibrosis. The diagnosis and treatment strategies targeting CEMIP are also summarized. The various functions of CEMIP show its great potential application value.